2017
DOI: 10.1002/stem.2669
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Non-Coding RNAs in Exosomes and Functional Efficacy of Human Embryonic Stem Cell- versus Induced Pluripotent Stem Cell-Derived Cardiomyocytes

Abstract: Background Both human embryonic stem cell-derived cardiomyocytes (ESC-CMs) and human induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) can serve as unlimited cell sources for cardiac regenerative therapy. However, the functional equivalency between human ESC-CMs and iPSC-CMs for cardiac regenerative therapy has not been demonstrated. Here we performed a head-to-head comparison of ESC-CMs and iPSC-CMs in their ability to restore cardiac function in a rat myocardial infarction (MI) model as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 28 publications
1
41
0
Order By: Relevance
“…Khan et al (2015) reported that ESCsderived exosomes, after being directly injected to infarcted mouse hearts, promote cardiac pro-angiogenesis and cardiomyocyte survival, improve cardiac function and reduce fibrosis after myocardial infarction. More recent papers confirmed the therapeutic effects of exosome in other types of myocardial injuries Singla et al, 2019) and explored the potential mechanism underlying the beneficial effects (Lee et al, 2017). The therapeutic delivery of exosomes through the circulation system by using miRNAs mimics or synthetic exosomes as cargos and vehicles have been widely studied.…”
Section: Exosomes From Stem Cellsmentioning
confidence: 98%
“…Khan et al (2015) reported that ESCsderived exosomes, after being directly injected to infarcted mouse hearts, promote cardiac pro-angiogenesis and cardiomyocyte survival, improve cardiac function and reduce fibrosis after myocardial infarction. More recent papers confirmed the therapeutic effects of exosome in other types of myocardial injuries Singla et al, 2019) and explored the potential mechanism underlying the beneficial effects (Lee et al, 2017). The therapeutic delivery of exosomes through the circulation system by using miRNAs mimics or synthetic exosomes as cargos and vehicles have been widely studied.…”
Section: Exosomes From Stem Cellsmentioning
confidence: 98%
“…These exosomes transported several upregulated miRNAs, including miR-92a which has been associated with antiapoptotic, proangiogenic, and antifibrotic effects. Lee et al (79) compared ESC-derived cardiomyocytes and iPSC-derived cardiomyocytes with respect to their ability to restore cardiac function in a rat MI model, as well as their exosomal secretome. Both cell types injected into nude rats post-MI comparably improved cardiac function.…”
Section: Cardioprotection By Exosomes From Ipsc-derived Cardiomyocytesmentioning
confidence: 99%
“…Extracellular vesicles (EVs), now identified as a novel apparatus of intercellular communication, did not garner significant attention previously, although they are currently sought after as a topic of research. EVs have a diameter ranging between 50 and 2,000 nm with a bilayer lipid membrane (1) and comprise parental cell-derived active cargos such as lipids (2), proteins (2,3), nucleic acids [(DNAs) (4), mRNA (5,6), microRNAs (miRNAs) (4), non-coding RNAs (7)] and organelles (4,8). Emerging evidence indicates that double-stranded DNA, DNA-binding histones, and certain miRNAs are not associated with small EVs such as exosomes (9).…”
Section: Introductionmentioning
confidence: 99%